(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This research study envisaged an extensive analysis of the impact of digitalization of banking operations on raising banking frauds and cyber frauds. The present technological savvy banking environment has offered wide range of facilities to its customers. By using these facilities a customer can conveniently pay and settle his due amounts while sitting at home or work place. Growing dependency on technology has offered many advantages but at the same time it is largely misused by many persons consequently responsible in raising frauds. Thus this research study has tried to covers the growing prospects of banking digitalization under the period of 2012-13 to 2018-19 and its impact on raising frauds. The study concluded with the significant impact of digitalization on raising banking frauds and cyber frauds in Indian banking sector.